An Exploratory Study of Washout Rate Analysis for Thallium-201 Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging Using Cadmium Zinc Telluride Detectors - Masaru Ishihara MS; Masahisa Onoguchi PhD; Takayuki Shibutani PhD (Molecular Imaging)
The aim of this study was to assess the washout rate (WOR) for thallium-201-chloride single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) using cadmium zinc telluride detectors for SPECT (CZT SPECT) versus conventional Anger-type SPECT (conventional SPECT). A total of 52 Japanese patients were examined using CZT SPECT and conventional SPECT, and the global WORs were compared. Additionally, the MPI WORs were compared for patients with a normal MPI versus those in whom MPI reflected the patients’ multivessel disease (MVD) MPI. Washout rates were similar when approximated by CZT SPECT versus conventional SPECT 12.59 ± 2.26%/h vs 12.57 ± 2.27%/h ( P = .997), respectively. The WOR values for CZT SPECT versus conventional SPECT were 13.42%/h (1.53%/h) vs 13.93%/h (1.24%/h) ( P = .337), respectively, for 7 normal MPI patients, and 10.64 ± 2.20%/h vs 10.84 ± 2.26%/h ( P = .848), respectively, for 7 MVD-MPI patients. The WOR values for normal MPI versus MVD-MPI patients for CZT SPECT were 13.42 ± 1.53%/h vs 10.64 ± 2.20%/h ( P = .025), respectively. Thallium-201-chloride WOR values obtained with high-efficiency CZT SPECT, which enabled significantly reduced imaging times and use of a low-dose protocol, were similar to those obtained with conventional SPECT.